2017
DOI: 10.1136/postgradmedj-2016-134694
|View full text |Cite
|
Sign up to set email alerts
|

Screening for developmental delay in preschool-aged children using parent-completed Ages and Stages Questionnaires: additional insights into child development

Abstract: The use of of parent-completed ASQs showed an overall prevalence of developmental delay in children aged 24-60 months of3.4%. Male gender, consanguinity and parental education were identified as risk factors for developmental delay. Family counselling about the child's developmental state is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
(7 reference statements)
4
11
0
Order By: Relevance
“…In our study, boys are at higher risk of developmental delay, and similar results were also found in Dutch, Norway, UK and Egypt among children aged 4-60 months, showing a significantly higher average ASQ score of girls especially in communication, personal social and fine motor domains (Abo El Elella et al 2017;Kerstjens et al 2009;Morley et al 2015;Richter ,Janson 2007). Low income is another high risk factor affecting the development of young children, which was also reflected in previous studies (Handal et al 2007;Noble et al 2015;Seguin et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, boys are at higher risk of developmental delay, and similar results were also found in Dutch, Norway, UK and Egypt among children aged 4-60 months, showing a significantly higher average ASQ score of girls especially in communication, personal social and fine motor domains (Abo El Elella et al 2017;Kerstjens et al 2009;Morley et al 2015;Richter ,Janson 2007). Low income is another high risk factor affecting the development of young children, which was also reflected in previous studies (Handal et al 2007;Noble et al 2015;Seguin et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Language development delay is one of the major concerns of parents in our society and worldwide that may lead to learning and social disabilities. Early diagnosis/ intervention is critical for future health benefits [22]. To our knowledge, this is the first study to describe this effect in language development in Egypt.…”
Section: Discussionmentioning
confidence: 85%
“…This percentage is similar to another Egyptian study that showed increased prevalence of cognitive delays and disorders in boys. The study showed that 73.5% children diagnosed with developmental delays were boys while 26.5% were girls [22].…”
Section: Discussionmentioning
confidence: 93%
“…Another barrier to early identification through screening revolves around the selection process of the screening instruments themselves (Drotar, Stancin, Dworkin, Sices, & Wood, ; Warren et al, ). Screening tools may be general, encompassing multiple domains (e.g., the Ages and Stages Questionnaire (ASQ‐3), Abo El Elella, Tawfik, Abo El Fotoh, & Barseem, ) or specific to a disorder such as autism (e.g., the Modified Checklist for Autism in Toddlers Revised with Follow‐up (M‐CHAT‐R/F); Robins et al, ). As awareness of concerns about child development and specifically autism has increased, screening has been widely encouraged to identify children with ASD or DD, accompanied by a large variety of instruments suggested in the literature (Moodie et al, ; Ringwalt, ; Rydz et al, ; Semrud‐Clikeman et al, ).…”
Section: Introductionmentioning
confidence: 99%